2014
DOI: 10.1111/ijcp.12594
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K and other markers of micronutrient status in morbidly obese patients before bariatric surgery

Abstract: Micronutrient status shows differing relationships with age, gender and BMI. Vitamin K insufficiency was present in 40% and not related to deficiencies in other vitamins or micronutrients. Vitamin D and vitamin K supplementation should be considered prebariatric surgery in patients with diabetes or severe insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Interestingly, the iron deficiency and anemia rates found in our study are considerably lower than those reported by studies carried out in other countries [10,11,13,33,37,40]. Low plasma iron concentrations found in our study are consistent with the low iron intake reported in the FFQ, as well as with the fact that the patients were mainly young women in reproductive age.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Interestingly, the iron deficiency and anemia rates found in our study are considerably lower than those reported by studies carried out in other countries [10,11,13,33,37,40]. Low plasma iron concentrations found in our study are consistent with the low iron intake reported in the FFQ, as well as with the fact that the patients were mainly young women in reproductive age.…”
Section: Discussionsupporting
confidence: 82%
“…However, such procedure carries the risk of complications, such as deficiencies for micronutrients, even when supplements are used [13,[28][29][30][31][32]. Moreover, obese patient often present with micronutrient deficiencies before to bariatric surgery [9][10][11][12][13][33][34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10][11] Nutritional deficiencies are commonly seen in patients presenting for bariatric surgery. 7,[12][13][14][15][16] Pre-existing micronutrient deficiencies prior to bariatric surgery, can involve poorer prognosis and postoperative complications. 13,15,16 Therefore, it is essential to screen and correct any abnormalities prior to surgery.…”
Section: Introductionmentioning
confidence: 99%